Religion and Addiction - Gostecnik, Christian (Journal of religion and health, 2012)
Religion with its rituals can become an object of addiction, especially when a child while growing up experiences neglect and abuse. It is also very common that such individuals transfer their feelings of anger, rage and sometimes even true hatred to God. Then God becomes the substitute for their displaced vengeance (upon those who abused them as children).